2002
DOI: 10.1164/rccm.2103118
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oral Neutrophil Elastase Inhibitor (ONO-6818) Inhibits Human Neutrophil Elastase-induced Emphysema in Rats

Abstract: We investigated the effects of a novel oral neutrophil elastase inhibitor (ONO-6818) on acute lung injury and pulmonary emphysema induced by human neutrophil elastase (HNE). Young male Wistar rats were divided into four treatment groups: (1) control group (saline); (2) HNE group (HNE 200 U + 0.5% carboxymethyl-cellulose [solution for ONO-6818]); (3) low-dose ONO-6818 group (HNE 200 U + ONO-6818 10 mg/kg); and (4) high-dose ONO-6818 group (HNE 200 U + ONO-6818 100 mg/kg). Saline and HNE were applied via the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…Such therapies are available or are under investigation in clinical trials, [24][25][26] highlighting the relevance of understanding the role that neutrophil elastase may play in disease initiation and progression. Studies of ibuprofen in older children and adults have shown a delayed decrease in lung function and improved maintenance of weight, with these findings attributed to antiinflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Such therapies are available or are under investigation in clinical trials, [24][25][26] highlighting the relevance of understanding the role that neutrophil elastase may play in disease initiation and progression. Studies of ibuprofen in older children and adults have shown a delayed decrease in lung function and improved maintenance of weight, with these findings attributed to antiinflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonally and immunologically guinea pigs are more like humans than other rodents; thus they are often used to model human infectious diseases [58]. Although rats are not as similar to humans they have been used to study a range of diseases such as emphysema [59], influenza [60] and pulmonary fibrosis [61]. Other systemic diseases such as diabetes can be induced in rats by administration of streptozocin [62].…”
Section: Animal Modelsmentioning
confidence: 99%
“…The neutrophil elastase (NE) was determined with a synthetic substrate, N-methoxysuccinyl-Ala-Ala-Pro-Val-p-nitroanilide as described previously [15,18]. In brief, samples were incubated in 0.1 M Tris-HCl buffer (pH 8.0) containing 0.5 M Nacl and 1 mM substrate at 37°C for 24 hrs.…”
Section: Methodsmentioning
confidence: 99%